Macroprudential Policy Framework: A Practice Guide - Krishnamurti, Damodaran (World Bank, 2015)
In the wake of the recent global financial crisis and against the backdrop of the ongoing global financial sector reforms, macroprudential policy is being increasingly seen as a ?must-do? reform. At the same time, some policy makers are keen on having a better understanding of what it is and how it works before they embark on implementing it.